2019
DOI: 10.1186/s12920-019-0618-0
|View full text |Cite
|
Sign up to set email alerts
|

Return of genetic and genomic research findings: experience of a pediatric biorepository

Abstract: BackgroundAssess process, uptake, validity and resource needs for return of actionable research findings to biobank participants.MethodsParticipants were prospectively enrolled in a multicenter biorepository of childhood onset heart disease. Clinically actionable research findings were reviewed by a Return of Research Results Committee (RRR) and returned to the physician or disclosed directly to the participant through a research genetic counselor. Action taken following receipt of this information was reviewe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 40 publications
2
27
0
Order By: Relevance
“…Overall, our findings that high confidence variants identified using in silico prediction models have functional consequences validates our bioinformatics approach to novel variant discovery and makes a strong case for exploring variants in recurrently mutated cis-regulatory elements of CMP genes in order to increase the yield of genetic testing 80,81 . In summary, our work provides a guiding strategy to address regulatory variants in cardiac disease and emphasizes the need for further research to validate the clinical utility of these findings.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Overall, our findings that high confidence variants identified using in silico prediction models have functional consequences validates our bioinformatics approach to novel variant discovery and makes a strong case for exploring variants in recurrently mutated cis-regulatory elements of CMP genes in order to increase the yield of genetic testing 80,81 . In summary, our work provides a guiding strategy to address regulatory variants in cardiac disease and emphasizes the need for further research to validate the clinical utility of these findings.…”
Section: Discussionsupporting
confidence: 66%
“…Ten cases (4.7%) died, and 130 cases (57%) experienced a major adverse cardiac event on follow-up ( Supplementary Table 1 ). Collection and use of human DNA and myocardial tissue from CMP cases through the Heart Centre Biobank Registry was approved by the Institutional Research Ethics Boards (Hospital for Sick Children, Children’s Hospital of Eastern Ontario, Toronto General Hospital, London Health Sciences Centre, Kingston General Hospital, and Hamilton Health Sciences Centre) and written informed consent was obtained from all patients and/or their parents / legal guardians 80,81 .…”
Section: Methodsmentioning
confidence: 99%
“…The key steps involved in the recontact and disclosure process included: (1) research sample validation; (2) recontact via US certified mail disclosing a DNA alteration that is potentially causing disease; (3) genetic counselor telephoned participants; (4) genetic counseling appointment; and (5) CLIA laboratory confirmatory genetic testing. Papaz et al [ 23 ] implemented a similar process among pediatric cardiovascular biobank participants (e.g., returning only actionable results, validating research samples prior to recontact). Our findings were comparable in regard to the uptake of genetic counseling (60%, 12/20 vs 55%, 11/20 reported here) and confirmatory genetic testing (100% 12/12 vs 91%, 10/11 reported here).…”
Section: Discussionmentioning
confidence: 99%
“…The average cost of those choosing to opt-in to genetic counseling and confirmatory genetic testing was $605. Other studies, including Papaz et al [ 23 ] and Christensen et al [ 9 ], reported an average cost of $750 and $679 per participant, respectively, to return clinically actionable research genetic results. This level of additional cost might lead some investigators to conclude that such an approach is not feasible.…”
Section: Discussionmentioning
confidence: 99%
“…These cardiac studies have shown that cardiac populations-including early adopters of genetic testing (Facio et al, 2013) and individuals with heart disease (Joffe et al, 2019)are highly interested in broad results. In a feasibility return of result study of a pediatric biorepository of early-onset heart disease, 86% of families who received actionable findings opted to pursue clinical follow-up with clinical genetics (Papaz et al, 2019). The primary objective of this study was to determine a) whether and what type of results participants with aortic disease would like to receive, and b) participant preferences for how results should be returned.…”
mentioning
confidence: 99%